2021
DOI: 10.3390/diagnostics11122189
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of 2-[18F]FDG PET/CT Metabolic Volume Parameters in Patients Affected by Differentiated Thyroid Carcinoma with High Thyroglobulin Level, Negative 131I WBS and Positive 2-[18F]-FDG PET/CT

Abstract: The clinical and prognostic role of 2-deoxy-2-[18F]fluoro-D-glucose positron emission tomography/computed tomography (2-[18F]FDG PET/CT) in the study of patients affected by differentiated thyroid carcinoma (DTC) with positive serum thyroglobulin (Tg) level and negative [131I] whole-body scan ([131I]WBS) has already been demonstrated. However, the potential prognostic role of semi-quantitative PET metabolic volume features, such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG), has not yet bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…12,15 FDG PET imaging has become increasingly important in management of patients with thyroid cancer, with FDG avid disease associated with poor prognosis. [16][17][18][19][20][21][22] FDG PET imaging have a role in detecting recurrence or persistent disease in both patients with negative WBS and elevated Tg (>10 ng/ml), and those with Tg < 10 ng/ml after initial treatment. 21,[23][24][25][26] The degree of FDG avidity has been associated with poor survival 5,17,25,27,28 and associated with poor response to RAI.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 FDG PET imaging has become increasingly important in management of patients with thyroid cancer, with FDG avid disease associated with poor prognosis. [16][17][18][19][20][21][22] FDG PET imaging have a role in detecting recurrence or persistent disease in both patients with negative WBS and elevated Tg (>10 ng/ml), and those with Tg < 10 ng/ml after initial treatment. 21,[23][24][25][26] The degree of FDG avidity has been associated with poor survival 5,17,25,27,28 and associated with poor response to RAI.…”
Section: Discussionmentioning
confidence: 99%
“…In this clinical setting, PET/CT parameters alone or combined with other prognostic factors can help to identify patients with poor outcomes [ 39 ]. Albano et al found that the only independent prognostic factors for overall survival were total metabolic tumor volume and total lesion glycolysis of all lesions with increased [ 18 F]FDG uptake [ 40 ].…”
Section: Non-iodine-related Pet Radiopharmaceuticalsmentioning
confidence: 99%
“…Thyroid scintigraphy with 99m Tc-pertechnetate enables the functional evaluation of the gland, allowing the differentiation between thyroiditis and hyperthyroidism, but also detecting the presence of ectopic thyroid tissue [4]. Moreover, 131 I is mandatory for the management of DTC, since its pivotal role for the therapy but also the stage or the restage of the disease [5][6][7][8][9]. Beside single photon imaging, positron emission tomography (PET) has continuously spread its indication for the evaluation of DTC and associated conditions, and in the recent years many different tracers have been proposed for the assessment of such diseases [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 131 I is mandatory for the management of DTC, since its pivotal role for the therapy but also the stage or the restage of the disease [5][6][7][8][9]. Beside single photon imaging, positron emission tomography (PET) has continuously spread its indication for the evaluation of DTC and associated conditions, and in the recent years many different tracers have been proposed for the assessment of such diseases [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%